Dental caries prevalence and bilateral occurrence in premolars and molars of adolescent school children in Ibadan, Nigeria (2015)
The aim of the study was to determine the prevalence of dental caries in premolars and molars of adolescent school children in Ibadan, Nigeria with a view of comparing findings from this study with previous African studies. A cross section of 12-19 year-old school children from the five local government areas in Ibadan were examined over a period of three months by two examiners (OD and DA), using the WHO criteria for diagnosing dental caries. Only premolars and molars were examined but the third molars were excluded because they were not fully erupted in most children. The mean age of the children under study was 16.2 ± 0.83 years. Dental caries was detected in 10.8% of the children. Overall, 225 teeth had dental caries, out of which 13.3% were premolars while 86.67% were molars. Among the molars, first molars were mostly affected by caries (68.72%) while 31.28% second molars were affected. Second premolars were more affected by caries among the premolars. Also bilateral caries occurrence was highest in the mandibular first molars. In conclusion since the first molars were the most vulnerable teeth to decay, caries preventive programs on them need to be drawn up.